المنهج الديني المتكامل الشريعة للسنة الرابعة - Awang Mat, Muhamad Zahiri; Sitiris, Miszairi; Abdullah, Mohd Tarmizi (Oxford Fajar Sdn. Bhd., 2017)
Form 4 Textbook for Religious Schools under the Ministry of Education of Malaysia.